Optimization of Criminal Fines as a Debt to the State to Enhance Non-Tax State Revenue under Law No. 1 of 2023 as an Instrument for State Financial Recovery - Anugrah R’lalana Sebayang; Sunaryo, Sunaryo; Heni Siswanto (Socio-Economic and Humanistic Aspects for Township and Industry, 2025)
The paradigmatic transformation of criminal fines within Law No. 1 of 2023 (the National Criminal Code) shifts its concept from a retributive sanction to an instrument of state financial recovery through the construction of "debt to the state." This reform addresses the systemic failure of the criminal fine system under the old Criminal Code, which was marked by irrelevant nominal values, the ineffectiveness of substitute imprisonment, and the resulting loss of potential Non-Tax State Revenue (PNBP). Employing a normative-juridical research method with a comparative approach, this article examines the philosophical, normative, and sociological foundations of this renewal. The primary finding indicates that the National Criminal Code—through its categorical fine system, consideration of the convict's ability to pay, and prioritization of asset execution—fundamentally alters the logic of penal fines. This innovation is theoretically capable of changing the rational calculus of convicts and significantly increasing PNBP. However, its implementation faces a crucial challenge in the form of a procedural law vacuum within the current Criminal Procedure Code (KUHAP), which fails to provide a procedural basis for prosecutors to conduct post-judgment execution seizures. While this reform has immense potential to significantly boost PNBP, its success is absolutely contingent upon the harmonization of the criminal procedure law to provide a robust procedural foundation for prosecutors as executors.